Evaluating the Effects of Experiencing Virtual Reality Simulation of Psychosis on Mental Illness Stigma, Empathy, and Knowledge in Medical Students - Zare-Bidaki, Majid; Ehteshampour, Alireza; Reisaliakbarighomi, Masoud; Mazinani, Robabeh; Khodaie Ardakani, Mohammad Reza; Mirabzadeh, Arash; Alikhani, Rosa; Noroozi, Mehdi; Momeni, Fereshteh; Samani, Amir Dehghani; Mehrabi Tavana, Mohammad Mahdi; Esmaeili, Aliakbar; et al. (Frontiers in Psychiatry, 2022)
Objectives: Applying technologies such as VR in education has gained popularity especially in comprehending abstract and subjective phenomena. Previous studies have shown that applying a virtual reality simulation of psychosis (VRSP) is useful in increasing knowledge and empathy towards patients. Here, the efficacy of using VRSP in altering stigma, empathy, and knowledge as well as side effects have been assessed in medical students in comparison with the routine education (visiting the patients). Method: After attending one session of lecture about positive psychotic symptoms, medical students were allocated to two groups: experiencing one session of VR Simulated Psychosis (VRSP) or visiting patients under supervision as for routine practice in the ward. Before and after the first session and after the second one, questionnaires of knowledge, empathy, and stigma were filled by students. Finally, the results were compared in two groups. Results: Both interventions were effective in reducing stigma as well as increasing knowledge and empathy toward patients with psychotic experiences. VRSP could significantly reduce stigma and increase knowledge and empathy compared with the traditional visiting patients under supervision. The side effects were minimal and ameliorated right after the experience. Conclusion: VRSP is an effective tool in decreasing stigma and increasing empathy and knowledge of the students and can be incorporated in psychiatric education with minimal side effects.